Capital Structure and Financing Decisions in Southeast Asia’s Property and Real Estate Sector: A Systematic Literature Review - Faisal Riza Rahman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This systematic literature review evaluates the existing research on capital structure and financing decisions within the property and real estate sector of Southeast Asia (ASEAN). Despite the sector's dynamic growth and substantial investments, the financial strategies specific to ASEAN remain minimally explored. A methodical review of scholarly articles from ScienceDirect, and Google Scholar spanning from 2000 to 2023. Our analysis identified prevalent themes and trends, notably the application of traditional capital structure theories such as pecking order and trade-off theories to more developed markets. However, the review highlights a significant gap in empirical research focusing on the unique economic, regulatory, and market conditions in ASEAN that crucially impact capital structure and financing choices in the region's property sector. The findings emphasize the need for more targeted empirical studies that account for the socio-economic diversity and specific institutional frameworks of ASEAN countries. These studies aim to enhance understanding of the financing behaviors in their property and real estate markets, thus aiding policymakers and investors in crafting informed strategies and policies.